The moderating role of posttraumatic growth on suicide risk among trauma exposed undergraduate students - Sheline, Kelly T., author; Rosén, Lee A., advisor; Swaim, Randall C., committee member; Henry, Kimberly L., committee member; Biringen, Zeynep, committee member (Colorado State University. Libraries, 2013)
Research has suggested that exposure to traumatic life events is one of the major risk factors for suicide. With suicide ranking as the second leading cause of death among college students, this study assessed the role that posttraumatic growth played in moderating the relationship between traumatic life events and suicidal ideation and behavior, suicide risk, and college adjustment in a sample of 557 undergraduate students. The results from multiple linear regression analyses showed that posttraumatic growth moderated the relationship between severity of traumatic life events and suicide risk such that individuals with the most severe traumatic life events were less likely to have high suicide risk in college if they had experienced posttraumatic growth following their trauma. In addition, posttraumatic growth moderated the relationship between severity of traumatic life events and college adjustment such that individuals with the most severe traumatic life events were more likely to have better college adjustment if they had experienced posttraumatic growth following their trauma. The role of posttraumatic growth in ameliorating the effects of trauma-inducing suicide and facilitating college adjustment has significant implications which are explored in the discussion.
Keywords: childhood maltreatment; moderator; posttraumatic growth; self report; suicide; trauma